The effect of leadership ethics and climate cooperation on job satisfaction of employees in education office of West Sumatera province - Nova Wilia; Nurhizrah Gistituati; Rifma (International Conferences on Educational, Social Sciences and Technology)
Field observations found that job satisfaction of employees in West Sumatera Provincial Education Office is still low. This is allegedly due to the influence of leadership ethics and cooperation climate, then conducted research to test the truth. This study aims to reveal the influence of leadership ethics and cooperation climate on employee job satisfaction in Education Office of West Sumatera Province. Hypothesis proposed in this research are: 1); there are influence of leadership ethics on cooperative climate, 2) there is influence of leadership ethics and cooperation climate to employee job satisfaction. Population in this research is all officer of Educational Department of West Sumatera Province with status of civil servant. The population is 300 people and the sample size is 73 people. Collecting data using Likert scale questionnaire that has validi and reabel. Data analysis using correlation and regression techniques. The result of data analysis shows that: 1) leadership ethics have an effect on cooperation climate equal to 63.50%, 2) leadership ethics influence to job satisfaction of employee equal to 55.80% and cooperation climate influence to employee job satisfaction equal to 37.40%.